Aktivitas Anticandida Herba Krokot (Portulaca grandiflora) - Agus Purwanto; Ch. Endang Purwaningsih; Christiana Indriasari (UNIVERSITAS PGRI MADIUN, 2022)
The purslane plant has been designated by the World Health Organization as one of the most widely used medicinal plants in the world and is known as